Exploring the Role of AI in Career Access Through a Social Justice Lens - Rachel Buchanan (Nordic Journal of Transitions, Careers and Guidance)
The purpose of this paper is to explore the social justice implications for career guidance of the emerging technologies of career access. Emerging recruitment and selection practices – such as Artificial Intelligence (AI) analysis of candidates’ social media presence and performance in interview, and the use of bots or virtual agents interacting with prospective candidates to evaluate, shortlist and profile them – demonstrate the complexity of contemporary career access in highly technological societies. Career guidance practice has become highly digitalised, and guidance practice likewise can include the use of AI. This paper compares the uses of AI in career guidance and in human resource management and provides an analysis of emerging practices through synthesis of the extant research. With the emerging practices sketched, the paper then outlines the social justice and ethical risks of the increased reliance on AI in career access. The analysis here highlights the need to consider how to avoid reinscribing existing inequities in the emerging digitalised processes of career access, education, and guidance. The nascent nature of AI augmented recruitment and guidance represents not only an educative opportunity for career guidance professionals but also suggests an advocacy role. As legislation and ethics around the use of AI for recruitment is underdeveloped there is an opportunity for career guidance professionals and educators to provide input into the ethical guidelines and regulation of the use of AI in employment and in their practice. Abstrakt Formålet med denne artikkelen er å undersøke hvilke konsekvenser de nye teknologiene for karriereveiledning har for sosial rettferdighet. Nye rekrutterings- og utvelgelsesmetoder – for eksempel kunstig intelligens (AI) som analyserer kandidatenes tilstedeværelse på sosiale medier og deres prestasjoner i intervjuer, og bruk av roboter eller virtuelle agenter som interagerer med potensielle kandidater for å evaluere, velge ut og profilere dem – viser kompleksiteten i dagens karriereveiledning i et høyteknologisk samfunn. Karriereveiledningspraksisen er blitt svært digitalisert, og veiledningspraksisen kan også omfatte bruk av kunstig intelligens. Denne artikkelen sammenligner bruken av kunstig intelligens i karriereveiledning og personalforvaltning og gir en analyse av nye praksiser gjennom en syntese av eksisterende forskning. Etter å ha skissert den nye praksisen, skisserer artikkelen de sosiale og etiske risikoene ved økt bruk av kunstig intelligens i karriereveiledningen. Analysen belyser behovet for å vurdere hvordan man kan unngå at de nye digitaliserte prosessene for karrieretilgang, utdanning og karriereveiledning gjenskaper eksisterende ulikheter. Det faktum at rekruttering og veiledning ved hjelp av kunstig intelligens er i sin spede begynnelse, representerer ikke bare en utdanningsmulighet for karriereveiledere, men også en mulighet til å påvirke. Ettersom lovgivningen og etikken rundt bruken av kunstig intelligens i rekrutteringsprosessen ennå ikke er ferdig utviklet, har karriereveiledere og lærere en mulighet til å bidra til utformingen av etiske retningslinjer. Nøkkelord: Kunstig intelligens; Rekruttering; Teknologi; Karriereveiledning; Sosial rettferdighet; Personalforvaltning